Al-I'laam wal-Qiyam: 'Alaaqatu Ihlaalin am Inhilaalin? (الإعلام والقيم: علاقة إحلال أم انحلال؟) - Salhi, Mostafa; SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUN, ISKANDI IAIN; Yunus, Ibrahim Aliyu (MEDIOVA: Journal of Islamic Media Studies, 2023)
This article attempts to shed light on the media’s relationship with the values that fall within the dialectic of influence and vulnerability, which is a stand-alone topic in media and communication science studies; within the framework of what is known as research studying the impact of media and communication on recipients. After standing on the value imperative, which is witnessing increasing interest in various research fields due to its importance and its existential nature, this imperative that is related to the nature of functions it undertakes within society, we moved to talk about the problem of values and the limits of convergence and nullity between them, highlighting the inability to judge the progress and backwardness of cultures. We then moved on to talking about intellectual and taste alienation, identity disorder and value degeneration fueled by the media, which contributed greatly to penetration or cultural invasion, in the absence of awareness of use, and fascination with the culture of others. We finish by talking about the transition from the value of media to informing values in an attempt to root for moral modernity, and to adopt a strategy that seeks to replace values instead of their dissolution. يحاول هذا المقال تسليط الضوء على علاقة الإعلام بالقيم التي تندرج ضمن جدلية التأثير والتأثر، وهو موضوع مستقل في دراسات الإعلام وعلوم الاتصال في إطار ما يعرف بالبحث الذي يدرس تأثير الإعلام والاتصال على المستفيدين. بعد الوقوف على حتمية القيمة، التي تشهد اهتمامًا متزايدًا بمجالات البحث المختلفة نظرًا لأهميتها وطبيعتها الوجودية، هذه الضرورة المرتبطة بطبيعة الوظائف التي تقوم بها داخل المجتمع، انتقلنا للحديث عن مشكلة القيم و حدود التقارب والتلاغي بينهما، وإبراز عدم القدرة على الحكم على تقدم الثقافات وتخلفها. ثم انتقلنا للحديث عن الاغتراب الفكري والذوقي، واضطراب الهوية وانحطاط أو انحلال القيمة الذي يغذيه الإعلام، مما يساهم بشكل كبير في الاختراق أو الغزو الثقافي، في ظل غياب الوعي بالاستخدام، والانبهار بثقافة الآخرين. ننتهي بالحديث عن الانتقال من قيمة الإعلام إلى القيم الإعلامية في محاولة للتجذير من أجل الحداثة الأخلاقية، واعتماد استراتيجية تسعى إلى إحلال القيم بدلاً من انحلالها.